2013
DOI: 10.3109/10903127.2013.804136
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic Myocardial Infarction Care with Fibrinolytics: a Process Map and Hazard Analysis

Abstract: In this mapping study of STEMI calls in which paramedics administer fibrinolytics, the process was found to be complex, containing many steps, but relatively few individual steps were highly hazardous to patient care or safety. This study has enabled specific actions to target the highest scoring hazard modes, in an effort to improve paramedic practice and patient safety for EMS STEMI patients. Key words: emergency medical services; myocardial infarction; fibrinolytic agents; ambulances; process map.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Several studies reported positive findings in hospital resulting from ‘advanced paramedic’ skills but these had only been applied during the pre-hospital phase such as clinical diagnoses of ST elevation MI [ 30 – 32 ] and paramedic-administered morphine or atropine [ 40 ] and fibrinolytic treatment [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported positive findings in hospital resulting from ‘advanced paramedic’ skills but these had only been applied during the pre-hospital phase such as clinical diagnoses of ST elevation MI [ 30 – 32 ] and paramedic-administered morphine or atropine [ 40 ] and fibrinolytic treatment [ 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…A previously published process map of Nova Scotia PHF identified all the actions and decisions required, and identified those which could be a risk. 7 This work provided insight into potential mitigation strategies. To date, system outcomes from this provincial cardiac reperfusion strategy have yet to be published.…”
Section: Introductionmentioning
confidence: 98%
“…Traditionally, paramedics transported patients to medical care, usually the closest emergency department. However, patient disposition options now include programs for critical care bypass of multiple trauma, acute cardiac and stroke patients (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), treat and release (22,15,17,33) and referral to other health and social service providers (15,18,33).…”
Section: Introductionmentioning
confidence: 99%